State level point-of-sale policy priority as a result of the FSPTCA - Sarah Moreland-Russell PhD MPH; Todd Combs PhD; Janice Jones MPH; Amy A. Sorg MPH (AIMS Press, 2015)
The Family Smoking Prevention and Tobacco Control Act (FSPTCA) give the U.S. Food and Drug Administration (FDA) unprecedented power to regulate tobacco products. One of the most significant provisions of the law allows state and local governments to adopt and enforce tobacco control legislation restricting the time, place, and manner (but not the content) of tobacco advertising. However, there is still reluctance among states and localities for mass adoption of laws due to challenges associated with legal feasibility and lack of U.S.-based evidence in effectiveness. The Center for Public Health Systems Science conducted interviews with key tobacco control contacts in 48 states at two time points (2012 and 2014) since the passage of the FSPTCA to assess the influence of the law on point-of-sale policy development in their state tobacco programs. Logistic regression results show that point-of-sale policy importance is growing post-FSPTCA, and that key influencers of this importance are states' tobacco control histories and environments, including that related to excise taxes and smoke free air policies. The adoption of smokefree and tax policies has become commonplace across the U.S., and the quality and extent of these laws and prevailing political will increasingly impact the ability of states to work in emerging tobacco control policy areas including those directed at the point of sale.